Using Klebsiella oxytoca bacteria to treat Sodium Lauryl Ether Sulfate (SLES) Pollution - Al-Zamili, Hussein Ali Awadh; Al-Mayaly, Ithar Kamil (Iraqi Journal of Science, 2025)
Sodium lauryl ether sulfate (SLES), a surfactant frequently incorporated into detergent formulations, typically ends up in wastewater treatment facilities after use. The present study aims to investigate the efficacy of bacteria isolated from Iraqi wastewater in removing SLES. Genetic analysis (16S rRNA) revealed that this strain is Klebsiella oxytoca. Three temperatures (30, 35 and 40) oC and pH values (5,7 and 9) were selected for this study, and three concentrations of SLES (25, 50, 100) mg/l were used. The SLES anionic surfactant demonstrated that the best biodegradation by Klebsiella oxytoca occurred at 30 oC and both pH 7 and 9, while the removal percentage for them was 98.32% and 95.4 %, respectively at 25 mg/l of SLES. The outcomes of this study revealed the potential and significance of SLES removal in actual effluents by aerobic biodegradation. The ability of this bacterium to degrade SLES makes it an important tool for bioremediation.